Preliminary low speed wind tunnel tests on a 70 degrees cropped delta wing with blowing at all edges - Alexander, A. J. (College of Aeronautics, 1960)
Wind tunnel tests have been made on a 70° Cropped Delta Wing with slot blowing from all edges in the plane of the wing. The tests include six-component force and moment measurements and the distribution of pressure at four chordwise stations on the upper surface. Some results are also given with slot blowing from one wing-tip. At a constant incidence blowing increases the size and strength of the leading edge vortices and moves the vortex cores outboard. It also eliminates the secondary separation. Extra non-linear lift is obtained from the increased vortex strength and the lift coefficient at a = 25 o is increased from 0.98 without blowing to 1,16 and 1.25 for C values of 0.123 and 0.278 respectively with blowing from all edges. The corresponding movement of the centre of pressure is less than one per cent of the root chord. If allowance is made for the wind-off jet drag due to the poor blowing distribution, the values of drag obtained with blowing at all edges are lower than those for the unblown case at a given lift and the resultant lift-to-drag ratios are much improved. Without blowing the maximum ratio is 6.5 at a CT of 0.13 but blowing from all edges with Ca's of 0.123 and 0.278 increases-this value to 13.8 and 18.7 respectively at approximately the same lift coefficient. At incidence, with blowing at all edges, the jet sheets roll up o form stable leading edge vortices but near zero incidence (a < 0.25°) the jet sheets oscillate from one surface to the other, due to a downwash lag effect, producing a sinusoidal lift.